Symmetry of differential equations of electromagnetic field in immovable medium - Tchaban, Vasyl (Publishing House of Lviv Polytechnic National University, 2012)
In the paper it is shown that differential equations describing an electromagnetic field in solid immovable media based on the vectors of intensities of electric or magnetic fields in most cases practically coincide with those based on the vector-potential of the electromagnetic field. This special feature essentially simplifies practical analysis, beginning with the determination of border conditions. The expressions for static and differential parameters of the medim are given. Показано, що диференціальні рівняння електромаґнетного поля в суцiльному нерухомому середовищі, записані стосовно векторів напружености електричного й маґнетного полів чи стосовно вектор-потенціалу електромаґнетного поля, у переважній більшості випадків збігаються за формою одне з одним. Ця особливість суттєво спрощує практичний аналіз, перш за все під кутом зору визначення крайових умов. Подаються вирази статичних і диференційних параметрів середовища.
Симетрія диференціальних рівнянь електромаґнітного поля в нерухомому середовищі
Keywords: differential equations; vectors and vector-potential of electromagnetic field; non-linearity; anisotropy; static and differential parameters; symmetry